Influence of the level of adhesive activity of Lactobacillus paracasei B-11821 bacteria on the effectiveness of the probiotic preparation for use in pig breeding - N.V. Pozolotina; I.V. Darmov; I.V. Marakulin; A.P. Pozolotin (Учёные записки Казанского университета: Серия Естественные науки)
The purpose of this paper is to reveal the relationship between the level of adhesive activity and the growth-stimulating effect of the probiotic strain L. paracasei B-11821 in the research and production experiment on wean piglets. For the above purpose, we have studied the influence of the probiotic preparation on the basis of both the highly adhesive strain L. paracasei B-11821 and the same strain with reduced level of adhesion on the intestinal microflora of weaned piglets, as well as on their daily weight increment and livestock safety. Weaned piglets aged (25 ? 5) days have been divided into three groups, with 30 piglets in each group. The first group has been given the probiotic preparation based on L. paracasei B-11821 with high level of adhesion ((50.7 ? 3.4)%), the second group has been given the preparation with reduced level of adhesion ((25.1 ? 10.0)%), the third group has been taken for control, i.e., piglets have not received the probiotic preparation. The results of the microbiological analysis of the intestinal microflora show that by the end of probiotic therapy the concentration of lacto- and bifidobacteria normalizes in the experimental groups, while in the control group it remains more than two points below the norm. The concentration of lactose-positive E. coli in the intestinal contents of weaned piglets at the end of the experiment corresponds to the norm in the first group and remains more than 3 points below the norm in the second and control groups. The concentration of non-pathogenic staphylococci in the first group remains within the norm and in the second and control groups is one point higher. In the experimental groups, no representatives of conditionally pathogenic microflora have been detected in contrast to the control group. If the strain with high level of adhesion is used, an increase is observed in the average daily weight increment (by 5.5%), live weight (by 5.3%), and livestock safety (by 6.7%) as compared to piglets which have been given the biopreparation on the basis of the strain with reduced level of adhesion. The economic effect per 1 ruble of cost is 11.51 and 5.66 rubles from using the preparation on the basis of highly adhesive culture and low-adhesive culture, respectively.